Seismic performance of Concentrically Braced Frames with non-buckling braces: A comparative study. (1st January 2018) - Qiu, Canxing; Zhang, Yichen; Li, Han; Qu, Bing; Hou, Hetao; Tian, Li
Highlights: The SMABs can be used as alternatives to the BRBs. The SMABs help mitigate residual inter-story drifts in CBFs. The SMABs enable the CBF to exhibit lower probabilities of failure. Abstract: Bucking-restrained braces (BRBs) can help limit the maximum transient inter-story drifts of Concentrically Braced Frames (CBFs) under earthquake loading, but they are not effective in mitigating the post-earthquake residual inter-story drifts in the CBFs. Shape Memory Alloys (SMAs) can exhibit flag-shape hysteretic loops with zero or negligible residual deformations under cyclic loading, suggesting their excellent superelasticity and energy dissipation capacity. With the limitation of the conventional BRBs and the favorable feature of the SMAs, it has been questioned that if the SMA braces (SMABs) can be used as alternatives to the conventional BRBs to further reduce the residual inter-story drifts while limiting the maximum transient inter-story drifts in CBFs. Focusing on a six-story demonstration CBF which has representative geometries, the SMABs were designed to enable the demonstration CBF to achieve similar maximum transient inter-story drift responses to the same CBF consisting of the BRBs under the design-level earthquake excitations. Seismic performances of the two designs (with the SMABs and the BRBs, respectively) were investigated through nonlinear static analyses and nonlinear response history analyses based on three suites of ground motion records representing different seismic hazard levels. Analysis results show that the SMABs are as effective as the BRBs in limiting the maximum transient inter-story drifts in the considered CBF but are more effective in reducing the residual inter-story drifts of the CBF. Moreover, it is found that the CBF with the SMABs can achieve a more uniform transient inter-story drift distribution in the system compared with the system consisting of the conventional BRBs. Finally, the advantage of the SMABs over the conventional BRBs is demonstrated through probabilistic analyses and interpretations of the results from the nonlinear response history analyses.